The importance of corporate real estate management to the corporation case study: Lembaga Tabung Haji / Mohd Nur Adnin Ibrahim - Ibrahim, Mohd Nur Adnin (2010)
As we all know, the rapid economic development has increase the needs for more spaces in conducting businesses. There are also many corporations involved in the economic development and this corporation needs real property or also known as corporate real estate in order to operate. Corporate real estate management is a supporting management function that helps the corporation in achieving their goals. There is no written form of understanding the importance of corporate real estate management. That is why the main aim of this project is to investigate the importance of corporate real estate management to the corporation in order to fully understand and see the potential of corporate real estate. Sources of data for this project comes from journals, newspaper articles, and also books and this is supported by people who are related to the field by using questionnaires and doing interviews. It is hoped that this project could clearly explain the importance of corporate real estate management and also explain on the risk involved in the management for the developing future of the corporate world.